2023
DOI: 10.3389/fendo.2023.1282584
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of teneligliptin in patients with type 2 diabetes mellitus: a Bayesian network meta-analysis

Miao Zhu,
Ruifang Guan,
Guo Ma

Abstract: BackgroundAs a popular antidiabetic drug, teneligliptin has been used for over 10 years, but its efficacy and safety have rarely been systematically evaluated. Therefore, a Bayesian network meta-analysis was conducted to evaluate the efficacy and safety of teneligliptin in patients with type 2 diabetes mellitus (T2DM).MethodsWe systematically searched PubMed, Web of Science, Embase, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov. Randomized controlled trials (RCTs) comparing teneliglipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similarly, the study conducted by Rizvi Jet.al, suggested that the majority of the diabetic patients were in the age groups of 41-60 years. 9 This was because aging disrupts the carbohydrate metabolism due to a decrease in insulin secretion in response to a glucose load, as well as increasing insulin resistance in peripheral tissues and insulin sensitivity diminishes with age and fat. 10 A total of 302 populations were incorporated in the data examination to assess the study's efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study conducted by Rizvi Jet.al, suggested that the majority of the diabetic patients were in the age groups of 41-60 years. 9 This was because aging disrupts the carbohydrate metabolism due to a decrease in insulin secretion in response to a glucose load, as well as increasing insulin resistance in peripheral tissues and insulin sensitivity diminishes with age and fat. 10 A total of 302 populations were incorporated in the data examination to assess the study's efficacy.…”
Section: Discussionmentioning
confidence: 99%